SURVEILLANCE, PRIVACY, AND SOCIAL MEDIA - Kibby, Marjorie; Fulton, Janet (AoIR Selected Papers of Internet Research, 2015)
The Millennial generation seems to be habituated to having immediate access to information, including essentially private information on people of interest to them. Social media has accustomed them to watching and being watched. Albrechtslund (2013) describes this type of surveillance as “participatory surveillance”, where people willingly keep watch on each other through social media. An anonymous focus group and online survey of 80 Australians aged between 18 and 34 investigated their use of participatory surveillance, that is, of their surveillance techniques on others and their awareness of the level of surveillance they themselves are under. The results reveal that while these young people were concerned about the privacy and security of their own personal information, they had come to rely on being able to access the personal information of others.